“We felt that something was not right”. Neoliberalism, Collateral Damage, and Discontent in Three of Diego Zúñiga’s Short Stories (Letras, 2025)
This article offers a reading of three short stories from Diego Zúñiga’s Niños héroes (2016) —“La ciudad de los niños,” “Un mundo de cosas frías,” and “Cabezas negras”— based on the hypothesis that their protagonists embody subjectivities shaped as “collateral victims” of the Chilean neoliberal model. The analysis is structured around three levels: the individual level, where precarious lives are portrayed; the institutional and spatial level, which exposes educational and urban inequality; and the relational-affective level, where bonds appear fractured or commodified. Drawing on Zygmunt Bauman, the stories reveal the liquid fragility of life horizons reduced to mere survival, while with Rita Laura Segato they illustrate how pedagogies of cruelty operate by turning exclusion into destiny. In this way, Zúñiga constructs a critical literary representation that reflects the social and cultural unrest that would culminate in Chile’s 2019 uprising.
Keywords: Neoliberalism; Discomfort; Collateral Damage; Diego Zúñiga